Modelos de puntuación crediticia: La falta de información y el uso de datos de una central de riesgos - Verónica Balzarotti; Fernando Castelpoggi (Banco Central de la República Argentina (BCRA), Investigaciones Económicas (ie), 2008)
– The main purpose of this paper is to study the problem created by the lack of information about the credit history of some debtors in the databases used to develop credit scoring models and the use of information about behavior compiled by a credit risk register as a potential solution to the problem. The paper analyzes two problems: (i) the need to provide a credit risk estimation of debtors whose behavior is unknown (because they are deleted from the databases without indication of the reason), and (ii) the assessment of the impact of ignoring these data when evaluating the credit risk of entities' portfolios. The fundamental strategy will be to allow the use of debtors' credit history in other entities, recorded in the credit risk register.
Keywords: C35; D81; G21; G28; 330; credit scoring; credit registers; credit risk; imputation; information sharing; missing data